A public database of macromolecular diffraction experiments. Issue 11 (1st November 2016) - Grabowski, Marek; Langner, Karol M.; Cymborowski, Marcin; Porebski, Przemyslaw J.; Sroka, Piotr; Zheng, Heping; Cooper, David R.; Zimmerman, Matthew D.; Elsliger, Marc-André; Burley, Stephen K.; Minor, Wladek
Abstract : The Integrated Resource for Reproducibility in Macromolecular Crystallography (IRRMC) is a large, scalable, and searchable web‐accessible archive of protein crystallography diffraction experiments organized according to metadata. Abstract : The low reproducibility of published experimental results in many scientific disciplines has recently garnered negative attention in scientific journals and the general media. Public transparency, including the availability of `raw' experimental data, will help to address growing concerns regarding scientific integrity. Macromolecular X‐ray crystallography has led the way in requiring the public dissemination of atomic coordinates and a wealth of experimental data, making the field one of the most reproducible in the biological sciences. However, there remains no mandate for public disclosure of the original diffraction data. The Integrated Resource for Reproducibility in Macromolecular Crystallography (IRRMC) has been developed to archive raw data from diffraction experiments and, equally importantly, to provide related metadata. Currently, the database of our resource contains data from 2920 macromolecular diffraction experiments (5767 data sets), accounting for around 3% of all depositions in the Protein Data Bank (PDB), with their corresponding partially curated metadata. IRRMC utilizes distributed storage implemented using a federated architecture of many independent storage servers, which provides both scalability and sustainability. The resource, which is accessible via the web portal athttp://www.proteindiffraction.org, can be searched using various criteria. All data are available for unrestricted access and download. The resource serves as a proof of concept and demonstrates the feasibility of archiving raw diffraction data and associated metadata from X‐ray crystallographic studies of biological macromolecules. The goal is to expand this resource and include data sets that failed to yield X‐ray structures in order to facilitate collaborative efforts that will improve protein structure‐determination methods and to ensure the availability of `orphan' data left behind for various reasons by individual investigators and/or extinct structural genomics projects.